2022
DOI: 10.3389/fimmu.2022.961197
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular histones aggravate autoimmune arthritis by lytic cell death

Abstract: Although recent studies have demonstrated a proinflammatory effect of extracellular histones in sepsis via endothelial cytotoxicity, little is known about their contribution to autoimmune arthritis. Therefore, we investigated the role of extracellular histones in autoimmune arthritis and their cytotoxic effect on synoviocytes and macrophages. We measured histones in the synovial fluid of patients with rheumatoid arthritis (RA) and evaluated arthritis severity in a serum-transfer arthritis (STA) mouse model wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…In this scenario, it has been reported that H2A caused damage not only to human primary epithelial and endothelial cells [ 21 ] but also to murine intestinal epithelial cells [ 45 ]. Furthermore, cell exposure to H2A resulted in the cell death of macrophages and synoviocytes in human patients with rheumatoid arthritis [ 46 ]. Additionally, high concentrations of extracellular histones in blood plasma were found to be correlated with the severity of COVID-19 [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, it has been reported that H2A caused damage not only to human primary epithelial and endothelial cells [ 21 ] but also to murine intestinal epithelial cells [ 45 ]. Furthermore, cell exposure to H2A resulted in the cell death of macrophages and synoviocytes in human patients with rheumatoid arthritis [ 46 ]. Additionally, high concentrations of extracellular histones in blood plasma were found to be correlated with the severity of COVID-19 [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…61 NET release can cause necrosis or apoptosis of various cells, including endothelium, 26,58 alveolar epithelium, 58 intestinal epithelium, 66 and synoviocytes. 35 Large aggregates of NETs can obstruct vessels and ducts. 40,61 Increased NET release has been detected in various infectious conditions.…”
Section: Full Scientific Reportmentioning
confidence: 99%
“…The leakage of soluble lysosomal enzymes into the cytoplasm occurs as a consequence of changes in lysosomal membrane stability and permeability, known as lysosomal membrane permeability (LMP) [ 35 ]. Previous studies have demonstrated that extracellular histones can increase plasma membrane permeability due to their direct cytotoxic effects [ [36] , [37] , [38] , [39] ]. Moreover, histones within the cytoplasm contribute to the instability of mitochondrial membranes [ [40] , [41] , [42] ].…”
Section: Introductionmentioning
confidence: 99%